1994
DOI: 10.2527/1994.72123110x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for preadipocyte proliferation during culture of subcutaneous and intramuscular adipose tissues from Angus and Wagyu crossbred steers

Abstract: The primary objective of this study was to provide evidence for preadipocyte proliferation during culture of adipose tissue explants; a secondary objective was to compare the lipogenic activity and cellularity of adipose tissues from American Wagyu crossbred steers. Subcutaneous (s.c.) and intramuscular (i.m.) adipose tissues were obtained at slaughter from the 2nd to 6th lumbar region of the loin from Angus (n = 10) and Wagyu crossbred steers (n = 10) that had been fed for 552 d by typical Japanese production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 27 publications
7
48
2
1
Order By: Relevance
“…In addition, double-muscled compared with conventional cattle and Charolais selected for high v. low muscle growth capacity have muscles with a higher proportion of fast glycolytic fibres (Cassar-Malek et al, 2005;Picard et al, 2006) and a lower intramuscular fat content (Gotoh et al, 2009), as observed Interaction between adipose tissue and muscle between genotypes with a high v. low lean-to-fat ratio (May et al, 1994;Bellmann et al, 2004). This is accompanied by a reduced expression of proteins related to oxidative and lipid metabolism in muscle (Bouley et al, 2005;Wang et al, 2005;Bonnet et al, 2007;Jurie et al, 2007;Graugnard et al, 2009).…”
Section: Nutritional and Physiological Control Of Muscular And At Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, double-muscled compared with conventional cattle and Charolais selected for high v. low muscle growth capacity have muscles with a higher proportion of fast glycolytic fibres (Cassar-Malek et al, 2005;Picard et al, 2006) and a lower intramuscular fat content (Gotoh et al, 2009), as observed Interaction between adipose tissue and muscle between genotypes with a high v. low lean-to-fat ratio (May et al, 1994;Bellmann et al, 2004). This is accompanied by a reduced expression of proteins related to oxidative and lipid metabolism in muscle (Bouley et al, 2005;Wang et al, 2005;Bonnet et al, 2007;Jurie et al, 2007;Graugnard et al, 2009).…”
Section: Nutritional and Physiological Control Of Muscular And At Growthmentioning
confidence: 99%
“…This is accompanied by a reduced expression of proteins related to oxidative and lipid metabolism in muscle (Bouley et al, 2005;Wang et al, 2005;Bonnet et al, 2007;Jurie et al, 2007;Graugnard et al, 2009). In several studies comparing pure or crossbred Pirenaican, Limousin, Holstein, Wagyu, Santa Gertrudis, Angus, and Japanese Black growing cattle it was repeatedly observed that the leaner breeds had lower adipocyte size in carcass and muscular WAT (Miller et al, 1991;May et al, 1994;Eguinoa et al, 2003), concomitant with lower gene expression of C/EBPs (Yamada et al, 2009) and PPARg (Bonnet et al, 2007), lipogenic activities (Hood and Allen, 1973;Miller et al, 1991;Eguinoa et al, 2003;Bonnet et al, 2007), leptin gene expression (Chilliard et al, 2005;Bonnet et al, 2007), and higher resistin (Komatsu et al, 2005) when slaughtered at similar age. However, when growing animals were slaughtered at different ages, but similar carcass adiposities, no differences between breeds persisted for gene expression of C/EBPs (Xu et al, 2009;Yamada et al, 2009), lipogenic activities (Chakrabarty and Romans, 1972;Eguinoa et al, 2003) or leptin gene expression (Chilliard et al, 2005).…”
Section: Nutritional and Physiological Control Of Muscular And At Growthmentioning
confidence: 99%
“…Some that have, include papers by Hood and Allen (1973), who compared young Holstein and Hereford £ Angus bulls the same age (14 months) and weight (275 kg carcass weight); Robelin (1981), who examined young Friesian and Charolais bulls at different maturity stages (15 to 65 percent of mature weight); Truscott et al (1983), who compared young Friesian and Hereford bulls at different ages (10,13,17, and 20 months), and May et al (1994) who compared Angus and Wagyu crossbed steers at 2 years of age. A review of the findings of these papers brings home the important influence of genotype on lipid accumulation, because the effect of genotype in all cases turns out to be significant at any given weight, age, or maturity stage.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, PPARs act as transcription factors to regulate gene expression by acting on lipid metabolism and adipocyte filling. Indeed, both C/EBPα and PPARγ from the IMF of Wagyu are increased when compared with the IMF of Angus cattle (May et al, 1994;Yamada et al, 2007;Duarte et al, 2013).…”
Section: Adipogenic Markersmentioning
confidence: 98%